Analysis of anti‐tumour necrosis factor‐induced skin lesions reveals strong T helper 1 activation with some distinct immunological characteristics3. (6th March 2018) - Stoffel, E.; Maier, H.; Riedl, E.; Brüggen, M.‐C.; Reininger, B.; Schaschinger, M.; Bangert, C.; Guenova, E.; Stingl, G.; Brunner, P.M.
Summary: Background: Psoriasiform and eczematous eruptions are the most common dermatological adverse reactions linked to anti‐tumour necrosis factor (TNF)‐α therapy. Yet, a detailed characterization of their immune phenotype is lacking. Objectives: To characterize anti‐TNF‐α‐induced inflammatory skin lesions at a histopathological, cellular and molecular level, compared with psoriasis, eczema (atopic dermatitis) and healthy control skin. Methods: Histopathological evaluation, gene expression (quantitative real‐time polymerase chain reaction) and computer‐assisted immunohistological studies (TissueFAXS) were performed on 19 skin biopsies from patients with inflammatory bowel disease ( n = 17) and rheumatoid arthritis ( n = 2) with new‐onset inflammatory skin lesions during anti‐TNF‐α‐therapy. Results: Although most biopsies showed a psoriasiform and/or spongiotic (eczematous) histopathological architecture, these lesions were inconsistent with either psoriasis or eczema on a molecular level using an established chemokine (C‐C motif) ligand 27/inducible nitric oxide synthase classifier. Despite some differences in immune skewing depending on the specific histopathological reaction pattern, all anti‐TNF‐α‐induced lesions showed strong interferon (IFN)‐γ activation, at higher levels than in psoriasis or eczema. IFN‐γ was most likely produced by CD3/CD4/Tbet‐positive T helper 1 lymphocytes. Conclusions: New‐onset anti‐TNF‐α‐induced eruptions previously classified as psoriasis or spongiotic dermatitis (eczema) exhibit a molecular profile that is different from either of these disorders. Abstract : What's already known about this topic? Psoriasiform and eczematous lesions are the most common skin adverse events of anti‐tumour necrosis factor‐α treatment, yet their immune profile remains to be elucidated. What does this study add? We found that these lesions are distinct from genuine psoriasis and eczema, but are uniformly characterized by a strong T helper 1 inflammatory signature. What is the translational message? The results might help to guide future treatment strategies for chronic inflammatory diseases preventing these side‐effects in the skin. Linked Comment:  Darrigade et al. Br J Dermatol 2018;178 :1007–1008 . Plain language summary available online Respond to this article